WHITHER ACCOUNTING? - Kerrigan, Harry D. (The Accounting Review, 1937)
The article presents the broad front of accounting activity in several sectors where accounting work is moving forward. These sectors may be referred to as the professional field, the field of private finance and industry, the field of public finance, and the educational field. The article discusses the matters common to the whole of accounting work, in fulfilling the purpose of accounting, that is, to exhibit the financial position of a particular unit of activity, and to exhibit the financial results of the particular unit over a length of time. All other purposes may be fairly subsumed under one or the other of these two and considered as auxiliary matters of varying importance according to the time, and place. Accounting provides refined classifications, use of averages, ratios, per unit figures, and cost and budgetary control, as aids to management and other special groups. Diverse as are the phenomena with which accounting deals, its two major objectives predominate and give the entire field a definite unity. In reaching these objectives use is made of a medium of expression, a body of working principles, and a technique.